Effectiveness of Effleurage Massage in Reducing Blood Pressure among Hypertensive Pregnant Women Aged 20–35 Years in Gorontalo - Yusni Podungge; Ika Suherlin; Sri Sujawati; Endah Yulianingsih; Anik Kurniawati; Asti Andriyani (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Hypertensive disorders in pregnancy (HDP) remain a major contributor to maternal mortality, particularly due to complications such as preeclampsia and eclampsia. According to the World Health Organization (WHO), approximately 585,000 maternal deaths occur annually, with more than half related to HDP. This study aimed to analyze the effect of effleurage massage on blood pressure in hypertensive pregnant women in Gorontalo City, Indonesia. A pre-experimental design with a one-group pretest–posttest approach was applied. Sixty pregnant women aged 20–39 years, with gestational age 20–36 weeks and systolic blood pressure ≥140 mmHg, were recruited through purposive sampling. Participants received effleurage massage on the upper body for 20 minutes daily over five consecutive days. Blood pressure was measured before and after intervention. Data were analyzed using paired t-tests. The results showed significant reductions in mean systolic blood pressure (from 146.9 ± 3.7 to 132.0 ± 4.0 mmHg; p = 0.000) and diastolic blood pressure (from 88.3 ± 4.0 to 77.6 ± 4.1 mmHg; p = 0.000). Effleurage massage demonstrated a consistent lowering effect across all participants. This non-pharmacological intervention may serve as a safe complementary approach to antenatal care for mild HDP. Future randomized controlled trials are recommended to confirm its efficacy and to explore maternal–fetal outcomes.